2007
DOI: 10.1590/s0034-71672007000100021
|View full text |Cite
|
Sign up to set email alerts
|

Guia de cuidados de enfermagem na prevenção da extubação acidental

Abstract: RESUMOArtigo que relata a experiência do emprego de um guia preventivo da extubação acidental que ocorre associada ao cuidado de enfermagem para os quatro momentos de maior incidência e que são: banho no leito, transporte, troca de fixação e mudança de decúbito. O conteúdo do guia está pautado nas recomendações encontradas em levantamento bibliográfico no MedLine e na experiência profissional. O guia vem sendo aplicado desde setembro de 2005. Espera-se que o guia contribua para diminuir cada vez mais a incidên… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…The scientific literature corroborates that using chest radiography has been discouraged as a standard to check OTT positioning due to the time and need for more specialized training, and its use at the bedside is not feasible (39) . Although bedside chest radiography in intensive care poses an additional risk of accidental extubation, as it requires patients to be lifted by a professional to place the X-ray plate at the level of the chest, its daily use provides the team with a strict control of OTT positioning (40) ; this may justify the evaluation of Brazilian experts. To avoid UPE caused by this intervention, nurses staying at the bedside to guide the head is essential (40) .…”
Section: Discussionmentioning
confidence: 99%
“…The scientific literature corroborates that using chest radiography has been discouraged as a standard to check OTT positioning due to the time and need for more specialized training, and its use at the bedside is not feasible (39) . Although bedside chest radiography in intensive care poses an additional risk of accidental extubation, as it requires patients to be lifted by a professional to place the X-ray plate at the level of the chest, its daily use provides the team with a strict control of OTT positioning (40) ; this may justify the evaluation of Brazilian experts. To avoid UPE caused by this intervention, nurses staying at the bedside to guide the head is essential (40) .…”
Section: Discussionmentioning
confidence: 99%
“…As to the dislocation of devices during the bed bath, only one reference was found in the literature, in the intensive therapy context, in which the risk of accidental extubation was identified during the bed bath, when changing position, transporting the patient and changing the fixation of the ventilation device. 10 During the bed bath, the patient is susceptible to infections, as his body is exposed and manipulated by the professionals' hand, which can act as contamination vehicles. In addition, the professionals performing the procedure are vulnerable to infections during the activity, as this is a moment of contact with the patient's body and with possible fluids and secretions.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have also found safety risks for the patients during the bed bath, such as the risk of falls, variation in the clinical condition and accidental extubation in the ICU context. 5,[9][10] In view of these studies that appoint body hygiene/bed bath as a determinant factor in the work load, but that do not go deeper into questions about how this work process takes place, besides the lack of studies on the theme, the objective in this study is to investigate the characteristics of the work organization of the nursing team related to care during the bed bath. The goal is to understand how this care is characterized and to deepen the knowledge on why it is considered a relevant factor in discussions on the workload.…”
Section: Introductionmentioning
confidence: 99%
“…The guide is based on four situations in which the nursing team is present: bathing in the bed, change of position, exchange of cannula fixation and transport of the patient. 1 The authors consider that the complications are greater in those patients in whom the accidental extubation was due to the nursing care, in other words, they happened in one of those moments and culminate in the increase of the work of the team and postponement of the discharge of the patient. Except for the exchange of fixation, all other reasons listed in the guide are a justification for the unplanned removal not only of orotracheal tubes and tracheostomy cannula, as well as other devices also mentioned in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the nursing team, in its uninterrupted care and constant vigilance, actively participates in the continuity of the therapy implemented. As part of nursing care, the prevention of complications due to the use of this type of technology, which is widely used in ICU, 1 should be discussed due to the significant avoidable morbidity and mortality and additional expenses. 2 Regarding the consequences of their unplanned removal, we can mention, for instance, injuries and increased length of stay in the unit, costs generated for the institution with treatment of injuries and infections, prolongation of hospitalization, adequate planning of nursing care and minimizing care-related risks.…”
Section: Introductionmentioning
confidence: 99%